Engagement in high- and low-rated argumentative essays: Interactions in Indonesian students’ writings - Handayani, Anis; Drajati, Nur Arifah; Ngadiso, N. (Indonesian Journal of Applied Linguistics, 2020)
This study reports the use of engagement in high-rated and low-rated EFL undergraduate students’ argumentative essays. The engagement here refers to one of the aspects in interacting with the readers, which is called metadiscourse (Hyland, 2005a). The data in this study were ten highest-rated and ten lowest-rated argumentative essays written by first-year undergraduate students. The data were coded manually by two raters to maintain data validity. The results reveal that high-rated essays contain less engagement than low-rated ones. However, it also shows that the engagement in high-rated essays was more varied and grammatically sophisticated than those in low-rated essays. Furthermore, while this study reveals that the higher number of engagement used in argumentative essays does not always coincide with the improved quality of the writing, it implies that the writing quality and score do not depend on the number of engagement expressed but more on the ways students use the engagement effectively. Thus, the explicit teaching on how to use engagement effectively in persuasive writings may be useful for the students to build more persuasive arguments as well as to improve their writing quality.